2010
DOI: 10.1021/om1005808
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ruthenium Boryl Analogues of the Shvo Metal−Ligand Bifunctional Catalyst

Abstract: Metal boryl complexes have received significant attention in the literature in recent years due to their role as key intermediates in a number of metal-catalyzed borylation reactions. The ligand scaffold is known to have a significant impact on the observed reactivity of these metal boryl complexes. A synthetic strategy to access ruthenium boryl analogues of the Shvo metal-ligand catalysts is described. Heating a precursor to Shvo's catalyst (1) with bis(catecholato)diboron at 50 °C provided ruthenium boryl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…The silica support, in the form of SBA-15 type MSN characterized by a hexagonal array (p6mm) of 9.7 nm diameter pores and a surface area of 385 m 2 /g, was produced by hydrolysis−condensation of tetramethylorthosilicate using the Pluronic P104 template, calcined at 550°C, washed with water, then heated at 550°C under vacuum, and subsequently stored in a glovebox away from ambient air and moisture. 44 The SiOH group surface concentration of 1.7 mmol/g was determined by measuring the concentration of toluene produced in a titration with Mg(CH 2 Ph) 2 (O 2 C 4 H 8 ) 2 53 and by spin counting of Q 3 -sites with 29 Si DPMAS NMR spectroscopy (1.6 mmol/g). Thusprepared MSN and Zr(NMe 2 ) 4 react in benzene at room temperature for 20 h producing Zr(NMe 2 ) n @MSN, a grafted material that we will contend is primarily monopodal tris(dimethylamido)zirconium, with smaller amounts of bipodal species bis(dimethylamido)zirconium and bis(dimethylamido) (dimethylamino)zirconium (eq 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The silica support, in the form of SBA-15 type MSN characterized by a hexagonal array (p6mm) of 9.7 nm diameter pores and a surface area of 385 m 2 /g, was produced by hydrolysis−condensation of tetramethylorthosilicate using the Pluronic P104 template, calcined at 550°C, washed with water, then heated at 550°C under vacuum, and subsequently stored in a glovebox away from ambient air and moisture. 44 The SiOH group surface concentration of 1.7 mmol/g was determined by measuring the concentration of toluene produced in a titration with Mg(CH 2 Ph) 2 (O 2 C 4 H 8 ) 2 53 and by spin counting of Q 3 -sites with 29 Si DPMAS NMR spectroscopy (1.6 mmol/g). Thusprepared MSN and Zr(NMe 2 ) 4 react in benzene at room temperature for 20 h producing Zr(NMe 2 ) n @MSN, a grafted material that we will contend is primarily monopodal tris(dimethylamido)zirconium, with smaller amounts of bipodal species bis(dimethylamido)zirconium and bis(dimethylamido) (dimethylamino)zirconium (eq 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…26 Hydroboration of aldehydes and ketones is catalyzed by soluble titanium, 27 molybdenum, 28 as well as a few late metal catalysts. 29,30 Recently, divalent germanium and tin compounds were also shown to catalyze this reaction, and hydrides were postulated intermediates. 31 Group 4-catalyzed carbonyl hydrosilylations and hydrogenations are also known, 11,32−35 and although Schwartz's reagent catalyzes hydroboration of alkynes, 36 we are not aware of previous reports of zirconium-catalyzed hydroboration of carbonyls.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are many types of ruthenium catalysts depending on the ligand attached to the metal; the most active one is the Shvo-type catalyst 133 . However, some disadvantages have been reported for the ruthenium catalyst, such as difficulty in its separation and reuse.…”
Section: Ruthenium (Ru)mentioning
confidence: 99%
“…By replacing the proton in the transition state with a Lewis acid, we propose to enable abstraction of hydrides from groups other than alcohols [28]. Our first plan to prepare a dual site ruthenium, boron hydride transfer catalyst was to functionalize Shvo's catalyst with a boronic ester as sketched in 4 (Scheme 1) [32]. Along these lines, Tim Clark has realized such a transition state with the Shvo scaffold in reduction chemistry, and has reported that 5 will catalyze aldehyde and aldimine hydroboration with a transition state such as 4 [33].…”
Section: Design Of a Dual Site Ruthenium Boron Catalystmentioning
confidence: 99%